2018
DOI: 10.1080/0886022x.2018.1456455
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitofilin in left ventricular hypertrophy in hemodialysis patients

Abstract: Left ventricular hypertrophy (LVH) is a common abnormality in hemodialysis (HD) patients. Mitochondrial dysfunction contributes to the progression of LVH. As an inner mitochondrial membrane structural protein, mitofilin plays a key role in maintaining mitochondrial structure and function. The aim of this study was to investigate the relationship between mitofilin and LVH in HD patients. A total of 98 HD patients and 32 healthy controls were included in the study. Serum N-terminal proBNP (NT-proBNP), endothelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Left ventricular mass is strongly related to efficacy of glucose and fatty acid oxidation by the mitochondria. 44 Mitochondrial DNA is inherited through the mother, which might explain why previous studies presented stronger motheroffspring left ventricular mass associations than father-offspring associations. 45 This is the first study to examine the association between parent-offspring fractional shortening.…”
Section: Discussionmentioning
confidence: 98%
“…Left ventricular mass is strongly related to efficacy of glucose and fatty acid oxidation by the mitochondria. 44 Mitochondrial DNA is inherited through the mother, which might explain why previous studies presented stronger motheroffspring left ventricular mass associations than father-offspring associations. 45 This is the first study to examine the association between parent-offspring fractional shortening.…”
Section: Discussionmentioning
confidence: 98%
“…The baseline clinical data of patients were collected, including gender, age, height and weight, and the body mass index (BMI) was calculated according to the following formula: BMI = weight (kg)/ [height (cm)] 2 . DBP and SBP of the patients measured by nurses in our hospital at admission were collected.…”
Section: Methodsmentioning
confidence: 99%
“…At present, its pathophysiological mechanism has not been fully clarified, but miRNAs have been verified to participate in cardiovascular pathophysiological processes such as heart development and remodeling, arrhythmia and myocardial hypertrophy. 2 Circulating miRNAs, i.e. miRNAs in serum and plasma, can maintain extremely high stability under harsh conditions such as high temperature, acidity and alkalinity together with RNase .…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, this MA‐5‐Mic60 effect yielded to increase mitochondrial ATP production and reduce ROS production, but without affecting respiratory chain activity or the respiratory complexes themselves (Suzuki et al, ). Adding to the necessity of Mic60 in normal kidney function, Wu et al () found in humans that, patients with hemodialysis had significantly less Mic60 expression compared with healthy volunteers, with the Mic60 expression decreasing even more in patients with kidney dialysis with heart left ventricle hypertrophy. These observations indicate that Mic60 may represent an important therapeutic target in kidney disease.…”
Section: Mic60 In the Kidneymentioning
confidence: 99%